Development of a Novel Support Modification for Efficient Lipase Immobilization: Preparation, Characterization, and Application for Bio-flavor Production - Moentamaria, Dwina; Irfin, Zakijah; Chumaidi, Achmad; Widjaja, Arief; Widjaja, Tri; Muharja, Maktum; Darmayanti, Rizki Fitria (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
The low cost and excellent catalytic properties of lipase for industrial processes are highly desirable. A promising new approach involves the support modification of lipase and spacer arm, which enables the enhancement of lipase properties. This study investigates the immobilization of crude lipase from Mucor miehei onto a Polyurethane Foam (PUF) surface using various coating techniques. The PUF matrix was obtained through isocyanate and polyol reactions. Subsequently, the PUF was coated by adsorbing lipase and adding edible support material. The immobilized lipase was then utilized in the hydrolysis of coconut oil to produce fatty acids. Furthermore, the immobilized enzyme was employed in the esterification of fatty acids to produce bio-flavors. The results demonstrate that the attachment reaction using support material, namely lecithin, gelatin, MgCl2, and Polyethylene glycol 6000 (PEG), all of which are simple and edible, was able to enhance the stability and reusability of lipase. This immobilization technique increased triglyceride hydrolysis into FFA by 422%. The successful edible support modification of immobilized lipase from M. miehei on PUF, coupled with significantly enhanced enzyme stability and catalytic activity, offers a promising, environmentally friendly solution for diverse applications in the food industry. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).